Clinton Health Plan Talking Points - SUSAN RIDGE (Tufts Archival Research Center, 2007)
Clinton Health Plan Talking Points and cover memo from Susan Stuntz. Outlines the basic structure of the plan and the regulatory structure. Asks and answers the questions, What are we buying, Who pays, and Whats questionable about this plan. Accuses plan of underestimating costs, being unrealistic, and placing limitations on the states.